2016
DOI: 10.1136/jramc-2016-000628
|View full text |Cite
|
Sign up to set email alerts
|

Tactical damage control resuscitation in austere military environments

Abstract: In tactical situations, in association with haemostatic procedures (tourniquet, suture, etc), tranexamic acid should be the first medication used according to the current guidelines. The use of fibrinogen concentrate should also be considered for patients in haemorrhagic shock, especially if point-of-care (POC) testing of haemostasis or shock severity is available. If POC evaluation is not available, it seems reasonable to still administer this treatment after clinical assessment, particularly if the evacuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 112 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…Current FMHS guidelines also include on‐site collection of “warm” fresh whole blood from prescreened donors . In our series, this procedure was used in Role 2 MTFs for seven casualties, with blood collection being performed by colocated Role 1 teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current FMHS guidelines also include on‐site collection of “warm” fresh whole blood from prescreened donors . In our series, this procedure was used in Role 2 MTFs for seven casualties, with blood collection being performed by colocated Role 1 teams.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and longer periods of care in austere settings further strengthen interest in field ultrasound capability to guide diagnosis and intervention. Similarly, it is likely that point‐of‐care laboratory tests (including lactate or coagulation, for example) could help to better guide remote damage control resuscitation …”
Section: Discussionmentioning
confidence: 99%
“…FWB has been used in military operations, especially in austere or far forward environments (Daniel et al , ), and evidence from the battlefield has shown favourable outcomes when compared to component therapy (Nessen et al , ). The military use an emergency donor panel for collection and delivery of FWB (Strandenes et al , ), and this provides rapid access to warm FWB in the vicinity of the patient, without need for storage, transport or refrigeration.…”
Section: Transfusion and Adjunctive Haemostatic Therapies For Trauma mentioning
confidence: 99%
“…The primary endpoint, 24-h transfusion volume, was not different between arms, although in a subgroup analysis there was significant reduction in transfusion need in patients without traumatic brain injury. FWB has been used in military operations, especially in austere or far forward environments (Daniel et al, 2016), and evidence from the battlefield has shown favourable outcomes when compared to component therapy (Nessen et al, 2013). The military use an emergency donor panel for collection and delivery of FWB , and this provides rapid access to warm FWB in the vicinity of the patient, without need for storage, transport or refrigeration.…”
Section: Whole Bloodmentioning
confidence: 99%
“…Bleeding during trauma kills 2 million people each year . Rapid and effective management of hemorrhage is critical to improving patient outcomes, and prevents development of secondary coagulopathies such as hyperfibrinolysis, which occur in many cases of polytrauma and prolonged field care during combat settings . This trauma‐induced coagulopathy is both common, occurring in 25% to 35% of trauma patients, and lethal, accounting for a four‐fold higher mortality rate than in patients without trauma‐induced coagulopathy .…”
Section: Introductionmentioning
confidence: 99%